A Real-Time Video Watermarking Algorithm for Authentication of Small-Business Wireless Surveillance Networks - Shaohui Liu; Daniel Bo-Wei Chen; Long Gong; Wen Ji; Sanghyun Seo (International Journal of Distributed Sensor Networks)
In some business applications, all kinds of cameras sensors are employed in a distributed way to capture videos for different tasks such as surveillance. Once some illegal actions happen, then somebody or some organization wants to forge or replace some surveillance video clips to destroy evidences or obtain illegal profits. How to authenticate the genuineness and integrity of the source video or trace the source of a video information leak becomes a growing requirement in these small businesses. Fortunately, video watermark just provides an effective technology to resolve this issue. This paper proposes a real-time video watermarking scheme for MPEG, where firstly exploits fast scenes segmentation to original video sequence and adaptively selects appropriate scenes to be embedded. Furthermore, visual model is utilized to modulate watermark strength. Watermarks are embedded by adjusting the number of bit1 in the bitstreams through changing level of run-level pairs. Experiment results show little loss of video quality and also exhibit excellent robustness against many attacks. As watermark is directly detected in bitstreams domain, real-time detection becomes a reality. In addition, the embedding strategy guarantees that the bit rate is not increased and the experiments also validate it.